Peran Minat Beli Dalam Memediasi Digital Marketing, Brand Awareness, Brand Ambassador, Online Customer Review Dan Citra Merek Terhadap Keputusan Pembelian Pengguna Scarlett Whitening - Vina Damayanti; Ari Siswati (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research aims to analyze and explain the impact of digital marketing and brand image on work interest as intervening variables. The data collection method was carried out through questionnaires to 100 Scarlett Whitening consumer respondents, using techniques of non-probability sampling. Data analysis was carried out using the multiple linear regression method. The research results show that there is a significant positive influence of the variables digital marketing on buying interest, while variable brand awareness also has a positive and significant effect on buying interest. The brand ambassador variable does not show a significant influence on purchasing interest, while the online customer review variable has a positive and significant influence on purchasing interest. Apart from that, the brand image variable also has a positive and significant effect on purchasing interest, as well as variable digital marketing, brand awareness, brand ambassador and brand image has a positive and significant effect on purchasing decisions, and online customer does not a significant influence on purchasing decisions. However, the purchase interest variable was not proven to be an intervening variable that mediates the influence of digital marketing, brand awareness, brand ambassador, online customer review and brand image on purchasing decisions.